The Urgency of Legal Regulation in Sustainable Business Practices - Yanti Yulianti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the critical role of legal regulation in promoting sustainable business practices, particularly in emerging economies facing institutional constraints. Using a qualitative, literature based approach grounded in thematic analysis, the research explores how legal frameworks influence corporate environmental, social, and governance (ESG) behavior across China, Indonesia, Brazil, and South Africa. Findings reveal that while mandatory ESG disclosures, environmental laws, and green fiscal incentives can positively shape corporate conduct, their effectiveness is highly dependent on enforcement consistency and institutional capacity. Multinational firms often lead in sustainability due to global regulatory pressures, while small and medium sized enterprises (SMEs) face structural challenges. The study also highlights the risks of greenwashing and regulatory arbitrage in jurisdictions with weak oversight. Moreover, international legal instruments such as the EU Deforestation Regulation and Paris Agreement are shown to influence domestic governance, although unevenly. The research concludes that to embed sustainability effectively, legal frameworks must not only be robust and adaptive but also supported by institutional legitimacy and stakeholder engagement. The study offers strategic policy insights for governments, regulators, and corporate leaders committed to advancing sustainable governance.